"And focused upon victims' needs": towards an assessment of the victim-friendly principles of restorative justice practice. Issue 3 (2nd July 2016) - Garbett, Claire
Abstract: Scholars and policy-makers typically laud restorative justice as being 'victim-friendly' in its rules and practices. High levels of victim satisfaction with its outcomes are put forward to substantiate this claim. However, there has been little research that engages with the constitutive role of restorative justice in shaping conceptions of identities, practices and needs. To address this gap, this article develops an analytic framework through which to assess the victim-friendly approach of restorative justice processes across social and legal contexts. In so doing, it engages with three key elements of restorative justice processes: firstly, how this justice approach conceives victims; secondly, how it shapes its practices (and not just outcomes) to address their concerns; and thirdly, how it responds to individual needs. The paper argues that engagement with the constitutive processes can bring a fresh perspective to the relationship between victims and restorative justice.